Hetero-Diels–Alder reactions of hetaryl and aryl thioketones with acetylenic dienophiles - Grzegorz Mlostoń; Paulina Grzelak; Maciej Mikina; Anthony Linden; Heinz Heimgartner (Beilstein Journal of Organic Chemistry, 2015)
Selected hetaryl and aryl thioketones react with acetylenecarboxylates under thermal conditions in the presence of LiClO4 or, alternatively, under high-pressure conditions (5 kbar) at room temperature yielding thiopyran derivatives. The hetero-Diels–Alder reaction occurs in a chemo- and regioselective manner. The initially formed [4 + 2] cycloadducts rearrange via a 1,3-hydrogen shift sequence to give the final products. The latter were smoothly oxidized by treatment with mCPBA to the corresponding sulfones.